Global tree mycorrhizal and leaf type co-influence inconsistent responses of leaf area to environmental factors - Yan Li; Zhaoyong Shi; Mingli Yuan; Zengmeihui Xu; Shuang Yang; Luping Ma; Yajie Sun; Shanwei Wu; Xin Zhang; Jiakai Gao (Ecological Indicators)
Leaf area reflects the adaptive strategies of plants to the environment. Mycorrhizae, as reciprocal symbionts of plants, significantly impact plant growth and development. Based on published literature, this study compiled a global database of leaf area of different mycorrhizal plants for woody plants, incorporating climate, soil, and geographic factors. We systematically investigated the differences in leaf area of two common mycorrhizal types (AM and ECM) across different climate zones and their responses to climatic and soil factors. Mycorrhizal type significantly influences global plant leaf area. In general, AM plants have larger leaf areas than ECM plants. Leaf area distribution exhibits a significant latitudinal gradient, decreasing from the equator to the poles. Analysis of covariance indicated that the interaction between mycorrhizal type and latitude significantly affects leaf area in compound and simple leaf plants but has no significant effect on total plant leaf area. Variance partitioning analysis (VPA) revealed differential leaf area responses in plants with different mycorrhizal types to climatic, soil, and geographic factors. These factors together explain 15.8–30.3 % of the variation in leaf area of AM plants and 35.9–75.8 % of the variation in ECM plants. Furthermore, the response of leaf area in different leaf types to environmental factors varies with mycorrhizal type across different climate zones. Clarifying the spatial driving factors and mechanisms underlying the variation in leaf area of plants with different mycorrhizal types is crucial. It has significant ecological implications for understanding plant–microbe interactions and plant growth and development.